Organizational Culture as a Mediating Variable in the Effect of Digital Competency and Work Environment on Employee Performance at the Regional Revenue Agency of West Lombok Regency - Gusti Ayu Desy Dwi Cahyani; Siti Nurmayanti; Akhmad Saufi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the role of organizational culture as a mediating variable in the relationship between digital competency, work environment, and employee performance at the Regional Revenue Agency (Badan Pendapatan Daerah/Bapenda) of West Lombok Regency, Indonesia. Employing a quantitative causal design, a census method was applied involving all 95 civil servants (Aparatur Sipil Negara/ASN) as respondents. Data were analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) via SmartPLS. The results demonstrate that digital competency positively and significantly affects both employee performance and organizational culture. Work environment does not directly affect employee performance, but significantly predicts organizational culture. Organizational culture positively and significantly affects employee performance, acting as a partial mediator between digital competency and performance, and as a full mediator between work environment and performance. These findings confirm that in bureaucratic organizations, work environment can only enhance employee performance by first strengthening organizational culture. Practically, this study emphasizes the importance of integrating digital competency development and conducive work environment creation as strategies to strengthen organizational culture for improving ASN performance.